RAP1 stimulates single- to double-strand association of yeast telomeric DNA: implications for telomere-telomere interactions. - Gilson, E (1994)
Repressor Activator Protein 1 (RAP1) of Saccharomyces cerevisiae is an abundant nuclear protein implicated in telomere length maintenance, transactivation, and in the establishment of silent chromatin domains. The RAP1 binding site 5' of the yeast HIS4 gene is also a region of hyperrecombination in meiosis. We report here that as RAP1 binds its recognition consensus, it appears to untwist double-stranded DNA, which we detect as the introduction of a negative supercoil in circularization assays. Coincident with the RAP1-dependent untwisting, we observe stimulation of the association of a single-stranded yeast telomeric sequence with its homologous double-stranded sequence in a supercoiled plasmid. This unusual distortion of the DNA double helix by RAP1 may contribute to the RAP1-dependent enhancement of recombination rates and promote non-duplex strand interactions at telomeres.